PENGARUH LITERASI KEUANGAN DAN INKLUSI KEUANGAN TERHADAP KINERJA USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI ERA DIGITALISASI PADA TOKO KELONTONG DI KECAMATAN KABUN - Ningsih Kusumawati; Makmur; Seprini (PT. Hasba Edukasi Mandiri, 2025)
This study aims to determine the effect of financial literacy and financial inclusion simultaneously on the performance of Micro, Small and Medium Enterprises (MSMEs) in the digitalization era at Grocery Stores in Kabun District. This study uses a type of quantitative research, where the research results can be processed using mathematical and statistical calculations. The population used in this study is the number of MSMEs according to the scale of business and Kabun District based on data from the UKM cooperative office, transmigration and labor of Rokan Hulu in 2021-2024 with a total of 2,267 MSMEs. The sampling technique used the slovin formula, with a sample size of 96 respondents. The data collection technique in this study was to distribute questionnaires, documentation, and interviews. The data analysis technique used SPSS ver.30 software. The results of this study indicate that the t test results show that financial literacy (X1) has a significant effect on the performance of MSMEs (Y), in the t test results financial inclusion (X2) also significantly affects the performance of MSMEs (Y) and the results of the f test show that financial literacy and financial inclusion have a significant effect simultaneously on the performance of MSMEs. It is known that the t test results which have the highest t value and beta coefficient are financial literacy, so that financial literacy has the strongest influence on MSME performance compared to financial inclusion.